Fenomena FOMO di Era Literasi Digital: Tantangan Pendidikan Islam bagi Generasi Muslim Milenial - Yayuk Primawati; Yogi Irawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The phenomenon of fear of missing out (FOMO) has become increasingly prominent in the era of digital literacy and poses a serious challenge for Islamic education, particularly in shaping the character of Muslim millennial generations. This study aims to analyze the impact of FOMO on the behavior, spirituality, and learning processes of Muslim youth, as well as to offer strategies for Islamic education in responding to this phenomenon. The research employed a qualitative method with a library research approach, through a critical review of books, journal articles, proceedings, and relevant research reports published in the last five to ten years. The findings indicate that FOMO affects not only psychological aspects but also leads to moral decline and spiritual crises among students. Islamic education plays a strategic role in addressing FOMO through the reinforcement of Islamic digital literacy, which includes critical awareness, media ethics, and self-control. The novelty of this study lies in emphasizing the need for repositioning Islamic education as a creative and transformative force capable of integrating the values of qana’ah, zuhud, and tawakkul into the digital reality, while offering an alternative paradigm in the form of joy of missing out (JOMO). Thus, this study concludes that Islamic education can serve both as a safeguard and as a guide for Muslim millennial generations to remain adaptive, critical, and rooted in transcendental values amid the dynamics of digitalization.